Secure localization scheme against wormhole attack for wireless sensor networks - Hong-long CHEN; Zhi-bo WANG; Zhi WANG; Jiang-ming XU; Yan-jun LI; Li-ping LIU (Tongxin xuebao)
As one of the key technologies in wireless sensor networks (WSN), localization is the basis of many WSN-based applications. However, WSNs are often deployed in the hostile environment, in which the attackers can eas-ily disrupt the localization procedure of the nodes. The effects of wormhole attack on the DV-Hop localization procedure are analyzed firstly, after which a secure localization scheme against the wormhole attack is proposed. The simulation re-sults illustrate that the proposed secure localization scheme can efficiently reduce the effects of the wormhole attack on the DV-Hop localization, which validates the effectiveness of the proposed scheme.